Hubungan Kontrasepsi Hormonal dengan Jumlah Perdarahan di Rumah Bersalin Sri Nirmala - Muslihati, Muslihati; Girsang, Bina Melvia; Herliawati, Herliawati (Jurnal Keperawatan Soedirman, 2016)
The hormonal contraception contains estrogen and progesterone. Hormonal contraception methods has a significant correlation with menstrual bleeding amount. The contributing factors were age, nutritional status, physical activity, and stress. This study aimed to determine the relationship between the hormonal contraception with the menstrual bleeding amount in Sri Nirmala Hospital. The study design was descriptive analytic. The sample size was 89 respondents. The study results showed that the majority of respondents used injection contraceptive method (55.1%); experienced abnormal menstrual bleeding (60.7%); age <40 years old (65.2%); normal nutritional status (62.9%); active physical activity (61.8%); experienced stress (61.8%). Menstrual bleeding amount was measured using a digital scale portable scale SF-400 during the 1st and 2nd day of menstruation. There was a significant relationship between hormonal contraception use (p=0.026), age (p=0018), nutritional status (p=0.007), physical activity (p=0016), and stress (p=0016) with menstrual bleeding amount. The hormonal contraceptive method has a significant correlation with menstrual bleeding amount.